UNIVERSITAS KLABAT NURSING STUDENT’S KNOWLEDGE AND ATTITUDES TOWARD PATIENTS LIVING WITH HIV/AIDS - Baitesda Suba (Jurnal Skolastik Keperawatan, 2015)
Introduction. Improving nurses and nursing student’s knowledge and attitudes toward patients with HIV/AIDS is vital for providing quality care to each patients. The purpose of this study is to identify the knowledge and the attitudes of nursing students toward patients living with HIV/AIDS. Methods. This descriptive cross-sectional study was conducted at Faculty of Nursing, Universitas Klabat (Unklab), Airmadidi. The inclusion criteria for the nursing students were as follows: being at least 18 years of age; being a fourth-year in course and as a nurse profession program nursing student; and having consent to participate in the research. The sample comprised of 90 nursing students. The study used two data collection tools: (1) the HIV/AIDS Knowledge Questionnaire and (2) the HIV/AIDS Attitude Questionnaire. Results. Participant’s knowledge were moderate or good, but they generally have negative attitude towards patients with HIV/AIDS. On the result of statistic test, there was no statistically significant relation between nursing students Â knowledge level and attitude scale toward patients with HIV/AIDS, Â Â Â p = 0.804 (p > 0,05). Conclusions. The current results reveal that nursing students have good knowledge of HIV/AIDS, but they have a negative attitude. Therefore their attitudes need to be improved.Keyword: HIV/AIDS, knowledge, attitudes, nursing studentÂ Full printable version: PDF